Outcomes and cost-effectiveness of different models of delivery of antiretroviral therapy - Leisegang, Rory (Department of Medicine, 2018)
Background: HIV remains a major contributor to the burden of disease in the Eastern and Southern African region, where around half of those with HIV/AIDS reside, according to the 2016 UNAIDS estimates. Data on the direct costs and outcomes of providing health care are important due to competing health needs and limited budgets in resource-limited settings, especially if we are to reach the UNAIDS 90-90-90 goals. This thesis presents a series of studies, which together represent the typical journey followed within an economic evaluation, starting with the establishment of a cohort, then onto cost and outcome analyses and, finally, the development of a Markov model for the purpose of establishing the cost-effectiveness of a particular intervention. Methods: Data for this thesis come from several cohorts within South Africa, with patients commencing ART between 1998 and 2014, and with care provided within a number of different models: private (Aid for AIDS), public-private partnerships or PPP (BroadReach), and public sector (Khayelitsha). The study design for all were retrospective cohort analyses. These cohorts had important strengths in their data: adherence measures (private, PPP); initiating ART at CD4 counts > 200 cells/µL (private); detailed cost data (private); long duration of follow-up with a larger proportion on second-line ART (private); ability to assess health care utilization pre-ART and in patient loss to ART follow-up (private); and availability of national identity numbers, allowing us to confirm mortality from national death register data (private, PPP). Results: The results sections of this thesis are presented in the form of published papers and chapters. In the first analysis (Chapter 4), we present a cohort profile for Aid for AIDS, where we describe the history of the programme and contrast it with the public sector programme in South Africa. In the second analysis (Chapter 5), we present a paper highlighting the profile and determinants of costs on ART over time in the private cohort. We draw attention to the impact of baseline stage and adherence to ART on early and late costs respectively. In the third analysis (Chapter 6), we explore different models of HIV care: GP versus clinic for public sector patients and courier versus collect pharmacy for private sector patients. In the third analysis (Chapter 7), we present a paper which reviews cost-effectiveness studies in LMICs and explores the relative impact of various factors on costs and mortality in preparation for the final analysis (Chapter 8), which required the development of a novel HIV Markov model. Conclusion: Interventions, such as public-private partnerships with GPs or home-refill by courier, which we have found to be associated with lower costs and improved outcomes respectively, should be considered for implementation in South Africa, especially in light of the proposed National Health Insurance. The focus of this thesis on models of ART delivery and the inclusion of under-represented or novel models are significant strengths.